Comparison of antifouling properties of native and invasive Sargassum (Fucales, Phaeophyceae) species. Issue 1 (2nd January 2017) - Schwartz, Nicole; Dobretsov, Sergey; Rohde, Sven; Schupp, Peter J.
Abstract: The invasiveness of algal species can be facilitated by chemo-ecological traits that allow the establishment of invasive species in a highly competitive environment. Anti-bacterial, anti-quorum sensing, anti-diatom and anti-larval properties of the invasive brown macroalga Sargassum muticum and three native Sargassum species from Oman waters were compared in laboratory and field experiments to assess whether these traits have the potential to facilitate the invasion process. Only the extract of S. muticum inhibited bacterial growth of four marine bacterial strains and quorum sensing in the reporter strain Chromobacterium violaceum CV017. Settlement, growth and survival of the diatom Cylindrotheca closterium and larvae of the bryozoan Bugula neritina were significantly inhibited by all Sargassum extracts in laboratory experiments. However, crude extracts of S. muticum had the strongest antifouling effect. Natural tissue-level concentrations of S. muticum extract reduced diatom density to about 20% compared with the controls. Larval mortality increased by 80–90% compared with controls with S. muticum extract diluted to one-third natural levels. Significant anti-diatom activity of S. muticum was confirmed in the field experiments with Sargassum extracts embedded in a phytagel matrix. Comparison of non-polar compounds by gas chromatography–mass spectrometry demonstrated that S. muticum extracts had overall fewer secondary metabolites but more species-unique compounds than extracts of native Sargassum spp. The greater antifouling defence of invasive vs . native Sargassum species indicates a selective trait that may contribute to the invasion success of S. muticum .